FRI0659 REMISSION PERSISTENCE IN RHEUMATOID ARTHRITIS, PSORIATIC ARTHRITIS AND AXIAL SPONDYLOARTHRITIS UNDER BIOLOGIC TREATMENT. (June 2019) - Ávila-Ribeiro, Pedro; Fonseca, Joao Eurico; Vieira-Sousa, Elsa
Abstract : Background: Patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA) under biologic treatment are increasingly achieving prolonged remission and tapering treatment is becoming standard practice. However, the optimal timing to start tapering remains unclear and predictors of loss of remission (LOR) are missing. Guidelines disagree on whether to wait for 6 or 12 months of sustained remission before tapering. Objectives: To determine whether longer sustained remission (6 versus 12 months) influences subsequent LOR rates and to identify predictors of LOR. Methods: We used the Rheumatic Diseases Portuguese Register (Reuma.pt), to identify RA, PsA and axSpA patients on stable biologic treatment in a single center and retrospectively analyze those who achieved sustained remission for at least 6 and 12 months. Survival analysis was used to characterize stability of remission and identify predictors of LOR. The Cox proportional hazards regression was stratified by diagnosis and adjusted for age, gender, smoking, baseline disease activity, type of biologic, previous switches and starting year of biologic treatment. Results: 195 patients (100 RA, 51 PsA and 44 AxSpA) of 1078 patients (785 RA, 116 PsA, 177 axSpA) registered in Reuma.pt at a single center and treated with biologics between 1999 and 2018, had at least one remission period with a minimal duration of 6 months. This corresponded to 310 individual remission periods longer than 6 months, 232 of which (74.8%) were longer than 12 months. Median remission time (since the start of remission period) was 78.6 weeks overall vs. 99.0 weeks for patients with a minimum 12 months remission (difference in median survival: 20.4 weeks). PsA patients showed significantly longer remission periods (p<0.0001), followed by axSpA and RA. We identified active smoking (HR 1.96, p=0.008 for the total population; HR 1.53, p=0.20; HR 7.42, p=0.01, HR 0.74, p=0.79 for RA, PsA and axSpA, respectively), and infliximab use (HR 2.23, p=0.005 for the total population; HR 4.07, p<0.001, HR 3.20, p=0.36, HR 0.62, p=0.62 for RA, PsA and axSpA, respectively; subcutaneous TNF inhibitors (TNFi) used as index category) to be significantly associated with LOR. A sensitivity analysis excluding infliximab patients further suggested female gender (HR 3.21, p=0.005) and duration of disease until first biologic (HR 1.05, p=0.031) as important co-variates. Conclusion: 6 vs. 12 months of sustained remission did not influence the subsequent rate of LOR. Smoking, the type of TNFi, female gender and duration of disease until biologic treatment were identified as predictors of LOR. Disclosure of Interests: Pedro Ávila-Ribeiro: None declared, Joao Eurico Fonseca: None declared, Elsa Vieira-Sousa Grant/research support from: MSD, Novartis